Psikoedukasi Anti Bullying pada Peserta Didik Kelas IX G SMP Negeri 20 Surakarta - Viony Rahmawati (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Bullying has become one of the most concerning social issues, particularly among children and adolescents. This community service activity in the form of anti-bullying psychoeducation aimed to enhance students' understanding of bullying, its impacts on both victims and perpetrators, and the importance of committing to preventing bullying behavior. The results of the activity demonstrated that psychoeducation successfully increased students' awareness of the importance of anti-bullying behavior, encouraged the development of empathy, and fostered positive attitude changes towards others. Active participation of students throughout the entire series of activities served as an indicator of the program's success. In conclusion, psychoeducation has proven to be an effective method for instilling anti-bullying values in students. This program had a positive impact by fostering a healthier school culture and supporting the development of students' character.